2013
DOI: 10.2478/s11534-013-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

Two methods to solve a fractional single phase moving boundary problem

Abstract: Abstract:A moving boundary problem of a melting problem is considered in this study. A mathematical model using the Caputo fractional derivative heat equation is proposed in the paper. Since moving boundary problems are difficult to solve for the exact solution, two methods are presented to approximate the evolution of the temperature. To simplify the computation, a similarity variable is adopted in order to reduce the partial differential equations to ordinary ones. PACS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Fractional moving boundary problems have gained in recent years great interest for the applications and these contributions have a potential significant impact because exact solutions and equivalence of different problems are provided. To have a complete review of the results in this field, as a reference for further studies to know the mathematical results obtained in literature and their applications, see [1], [10], [11], [12], [18], [19]. An interesting physical meaning of the fractional Stefan's problems is discussed in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional moving boundary problems have gained in recent years great interest for the applications and these contributions have a potential significant impact because exact solutions and equivalence of different problems are provided. To have a complete review of the results in this field, as a reference for further studies to know the mathematical results obtained in literature and their applications, see [1], [10], [11], [12], [18], [19]. An interesting physical meaning of the fractional Stefan's problems is discussed in [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some advances in this direction were recently given in [13]. Looking for approximate solutions (both numerical and analytical) is an active area of research, [3,6,7,16,17,25,33,38,40].…”
Section: Brief Review On Time-fractional Stefan Problemsmentioning
confidence: 99%
“…Timefractional conservation equations were also considered in [5], where the relation with non-local transport theory with memory effects is discussed. In this way, we provide a new approach to derive some fractional problems that are of interest in pure and applied fields, [2,3,6,7,13,16,17,19,25,33,[38][39][40].…”
mentioning
confidence: 99%
“…A particular approach of promise, that has a theoretical bases in generalized Brownian motion (Metzler and Klafter, 2000;Schumer et al, 2009), is the use of fractional calculus (Podlubny, 1999;Meerschaert and Sikorskii, 2012); essentially the transient and flux components in the governing transport equations are molded in terms of time and space convolutions representing memory and non-locality, respectively. In this way, a number of authors (Voller, 2010(Voller, , 2012(Voller, , 2014Voller et al, 2013;Liu and Xu, 2009;Li et al, 2013;Atkinson, 2012) have investigated the predictive consequences of replacing the transient and flux terms in standard heat conduction phase change models with fractional derivative counterparts. And indeed, it has been shown that such replacements do lead to anomalous behavior.…”
mentioning
confidence: 99%